Hubungan Kuliah Daring dan Minat Belajar dengan Prestasi Belajar Mahasiswa Pendidikan Teknik Elektro - Kamagi, Waraney; Memah, Viverdy; Ticoh, Janne (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2021)
This study aims to: (1) analyze the relationship between online lectures and academic achievement in the 1st semester of Electrical Engineering Education, Manado State University; (2) analyze the relationship between interest and learning achievement in the 1st semester of Electrical Engineering Education, Manado State University; (3) analyzing the relationship between online lectures and interest in learning together with learning achievement. This study uses a correlational quantitative method approach that aims to obtain a systematic, factual, and accurate design; by describing the relationships between the independent or independent variables (X1, X2) and the dependent or dependent variable (Y); and how big is the level of correlation between the variables based on the correlation coefficient. Based on research on the relationship between online lectures and interest in learning with learning achievement in the 1st semester of Electrical Engineering Education, Manado State University that the level of relationship between online lectures and learning achievement, interest in learning and learning achievement, as well as the relationship between online lectures and interest in learning together with learning achievement that has a strong correlation level. AbstrakÃ¢â‚¬â€ Penelitian ini bertujuan untuk: (1) menganalisis hubungan kuliah daring dengan prestasi belajar mata kuliah bidang studi semester 1 Pendidikan Teknik Elektro Universitas Negeri Manado; (2) menganalisis hubungan minat dengan prestasi belajar mata kuliah bidang studi semester 1 Pendidikan Teknik Elektro Universitas Negeri Manado; (3) menganalisis hubungan kuliah daring dan minat belajar secara bersama-sama dengan prestasi belajar. Dalam penelitian ini menggunakan pendekatan metode kuantitatif korelasional yang bertujuan untuk mendapatkan rancangan secara sistematis, faktual dan akurat; dengan mendeskripsikan hubungan-hubungan antara variabel indepeden atau bebas (X1, X2) dan variabel dependen atau terikat (Y); serta seberapa besar tingkat korelasi antara variabel-variabel berdasarkan koefisien korelasi. Berdasarkan penelitian tentang hubungan kuliah daring dan minat belajar dengan prestasi belajar mata kuliah bidang studi semester 1 Pendidikan Teknik Elektro Universitas Negeri Manado bahwa tingkat hubungan kuliah daring dengan prestasi belajar, minat belajar dengan prestasi belajar, serta hubungan kuliah daring dan minat belajar secara bersama-sama dengan prestasi belajar yaitu mempunyai tingkat korelasi yang kuat.